SERVICE QUALITY CONTROL IN SAUDI ARABIAN AIRLINES - Author; Nasrin Rahmati (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study aimed to reflect the significance of service quality control management in the special reference of Saudi Arabian Airlines. The primary information is collected with the help of survey through questionnaire method. Survey through questionnaire method has been used for the purpose of revealing primary data related to the study context. Second method of data collection used was literature review method. A total of 100 questionnaires were distributed among the passenger, out of which 78 were returned. Rest 15 questionnaire were rejected as not filled properly. In the study, the survey is done with 63 passengers who have recently travelled with Saudi Arabian Airlines. These passengers travelled with Saudi airlines can provide some crucial information with the positive and negative aspects of the service quality of the Saudi Arabia. In addition, this study was used graphical representation. The result indicated the significance of establishing an effective service quality control framework for Saudi Arabian Airlines